The polychlorinated dibenzofuran fingerprint of iron ore sinter plant: Its persistence with suppressant and alternative fuel addition. (July 2016) - Thompson, Dennis; Ooi, Tze C.; Anderson, David R.; Fisher, Ray; Ewan, Bruce C.R.
Abstract: An earlier demonstration that the relative concentrations of isomers of polychlorinated dibenzofuran do not vary as the flamefront of an iron ore sinter plant progresses through the bed, and profiles are similar for two sinter strands has been widened to include studies of the similarity or otherwise between full scale strand and sinter pot profiles, effect of addition of suppressants and of coke fuel substitution with other combustible materials. For dioxin suppressant addition, a study of the whole of the tetra- penta- and hexaCDF isomer range as separated by the DB5MS chromatography column, indicates no significant change in profile: examination of the ratios of the targeted penta- and hexaCDF isomers suggests the profile is similarly unaffected by coke fuel replacement. Addition of KCl at varied levels has also been shown to have no effect on the 'fingerprint' and there is no indication of any effect by the composition of the sinter mix. The recently published full elution sequence for the DB5MS column is applied to the results obtained using this column. It is confirmed that isomers with 1, 9-substitution of chlorine atoms are invariably formed in low concentrations. This is consistent with strong interaction between the 1 and 9 substituted chlorine atoms predicted by DFT thermodynamic calculations. Non-1, 9-substituted PCDF equilibrium isomer distributions based on DFT-derived thermodynamic data differ considerably from stack gas distributions obtained using SP2331 column separation. A brief preliminary study indicates the same conclusions (apart from the 1, 9-interaction effect) hold for the much smaller content of PCDD. Highlights: Sinter pot and full scale iron ore sinter strand PCDF isomer profiles are similar. Full isomer profiles with and without suppressants are shown to be similar. Targeted isomer ratios are shown to be unaffected by coke fuel replacement. Observed and DFT-predicted 1, 9-substituted isomer abundances are low. Observed non-1, 9PCDF isomer abundances do not match DFT-based levels.